2016
DOI: 10.1017/s1041610216001848
|View full text |Cite
|
Sign up to set email alerts
|

Suicide in older adults: a comparison with middle-aged adults using the Queensland Suicide Register

Abstract: Our findings show older adults who died by suicide were more likely to experience somatic illnesses, bereavement, and pay attention to suicide in the media compared to middle aged. Preventing suicide in older adults would therefore require holistic and comprehensive approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 24 publications
(28 reference statements)
1
21
1
1
Order By: Relevance
“…Our results showed that alcohol use disorder or suicide attempt in a drunken state was not frequent in older groups. Some studies have reported a low prevalence of alcohol use disorder in elderly suicide attempters and completers . It may be a reflection of lower drinking prevalence in the older population .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showed that alcohol use disorder or suicide attempt in a drunken state was not frequent in older groups. Some studies have reported a low prevalence of alcohol use disorder in elderly suicide attempters and completers . It may be a reflection of lower drinking prevalence in the older population .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported a low prevalence of alcohol use disorder in elderly suicide attempters and completers. 9,14,17,35 It may be a reflection of lower drinking prevalence in the older population. 36,37 But a previous study indicated that although suicide attempt in a drunken state was not frequent, older attempters were as impulsive as the younger group.…”
Section: Affiliatedmentioning
confidence: 99%
“…This observation is consistent with the recently published study out of Spain 11 . Global and national trends and the Parra-Uribe study indicate that suicide rates increase with age and peak in older adults 59 . Using our deep learning methodology with a dataset that includes actual suicides in the Berkshire population may provide important insights into the difference between risk factors for suicide attempt and risk factors for completed suicide.…”
Section: Age-related Feature Differencementioning
confidence: 99%
“…5 This age group is less likely to experience somatic illness and healthrelated life events than the older adults. 5 Although the above-cited studies recognise important factors operating in close proximity to suicide, a life-course perspective is also important when planning interventions and evaluating suicide risk in clinical settings since distal factors may play a role in susceptibility to suicide later in life. 3,[6][7][8][9] A study of the 1958 British birth cohort with a follow-up time of 8-49 years reported both prenatal and early childhood risk factors for suicide.…”
mentioning
confidence: 99%